Sistem Informasi Eksekutif Aplikasi Rumah Sakit Berbasis Web & Mobile System ( Studi Kasus : Rs. Tugurejo Semarang ) - Ritonga, Roy Amrullah; Megayanti, Anita (University of Muhammadiyah Tangerang, 2020)
Hospital Application Executive Information System is a system that provides information for executives about the overall performance of a company or agency.Hospital has the function and objective of health service facilities which provide service activities in the form of outpatient services, inpatient services, emergency services, referral services which include medical record services and medical support and are used for education, training and research for health workers. With the existence of this executive information system, it becomes a combination of the Management Information System (MIS) with the Decision Support System (DSS) and AIat to help executives identify the basis of a problem and find a solution.So it is not impossible that the executives of Tugurejo Hospital need information that is useful, accurate and fast. However, based on the survey and interviews the author conducted, it was found that executives at these hospitals took a long time to get accurate information. This was partly due to the difficulties in functioning at the time of data collection, because the source data were not well organized and were still separated from one another, manual recording was still done and the lack of executive support facilities required for information. The right solution to solve this problem is to create an Executive Information System application based on web & mobile systems.With the development of a web & mobile-based Executive Information System this system is intended to help provide the information needed by Rs executives. Tugurejo to analyze or monitor the development of tugurejo hospital services in Semarang City that are faster and more focused through reports in the form of graphs or tables that can drilldown to a more specific level, so that the information received can be more easily understood and can see detailed information and can be accessed anywhere without time and space limits. While the method used to analyze the problem is the Fishbone Diagram.Keywords— Executive Information Systems, Mobile Application systems, fishbone diagrams, Management Information Systems, Decision Support Systems.